The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.3390/su11154032
|View full text |Cite
|
Sign up to set email alerts
|

Urban Vitality Area Identification and Pattern Analysis from the Perspective of Time and Space Fusion

Abstract: Urban vitality provides an important basis for evaluating urban development and spatial balance. In the era of big data, the quantitative analysis of urban vitality has become a research hotspot in the field of urban sustainability and planning research. However, time variation characteristics are often neglected, which leads to one-sidedness in the pattern analysis of urban vitality. In this paper, a method for extracting vitality areas and integrating spatiotemporal features clustering is proposed. The metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 40 publications
2
33
1
Order By: Relevance
“…We found that the vitality of most streets in the main urban area of Xining city was characterized by low intensity and low stability, and that vitality intensity on weekdays and weekends was similar; however, street vitality stability increased significantly on weekends. While previous studies have shown that the spatial concentration and orderliness of land use have a significant impact on vitality [53], we found that land use concentration was positively related to street vitality intensity, and its richness and uniformity were positively related to street vitality stability. Superior shopping, life, catering, and transportation services appeared on these high-intensity vitality streets, which confirm the previous findings that convenient traffic conditions are an important driving force for vitality [11].…”
Section: Discussioncontrasting
confidence: 95%
“…We found that the vitality of most streets in the main urban area of Xining city was characterized by low intensity and low stability, and that vitality intensity on weekdays and weekends was similar; however, street vitality stability increased significantly on weekends. While previous studies have shown that the spatial concentration and orderliness of land use have a significant impact on vitality [53], we found that land use concentration was positively related to street vitality intensity, and its richness and uniformity were positively related to street vitality stability. Superior shopping, life, catering, and transportation services appeared on these high-intensity vitality streets, which confirm the previous findings that convenient traffic conditions are an important driving force for vitality [11].…”
Section: Discussioncontrasting
confidence: 95%
“…This study also demonstrates how appropriately designed and formulated physical environments can attract and amplify people's attention, although their importance and relevance may differ according to regional characteristics. By individually examining the three city centers, the results indicated that increases in development capacity were not the solution for vitalizing commercial activities or attracting people; rather, development programs that consider high accessibility to public transportation or well-designed pedestrian areas, depending on the region, might be more effective [1,3,4,9,16,19,20,29,41].…”
Section: Discussionmentioning
confidence: 99%
“…The factors described in Table 1 were also used in this analysis and included socioeconomic factors, land use mix, development capacity, access to public transportation, access to green space/attractions, and adjacent roads and terrain conditions, with a total of 15 sub-components. These factors were used in the analysis because several former successful studies also considered these [1,2,4,8,16,17,19,20,35,41]. In addition, these variables were selected as independent of each other, and the VIF values between these variables were confirmed.…”
Section: Data Sources and Variablesmentioning
confidence: 99%
“…For example, He found that in areas with a high population density and urban function mixing degree, office-type functional areas should be added [ 21 ]. Liu [ 22 ] used mobile phone data collected over a week, combined with the land use characteristics of POIs, and integrated this with the spatial-temporal feature clustering method to calculate the density and spatial entropy of POIs, thereby measuring the urban function mixing degree and finding a strong correlation between it and urban development.…”
Section: Literature Reviewmentioning
confidence: 99%